2020
DOI: 10.1111/1750-3841.15001
|View full text |Cite
|
Sign up to set email alerts
|

Volatile composition of prickly pear fruit pulp from six Spanish cultivars

Abstract: This research analyzed the volatile composition of the fruits pulp of six prickly pear cultivars (NT, NE, NO, NA, FR, and ORI) growing in Spain, by headspace solid-phase microextraction and gas chromatography (GC-MS and GC-FID). A total of 35 compounds were isolated, identified, and quantified, with aldehydes, alcohols, and terpenes being the predominant chemical families, and esters, ketones, linear hydrocarbons, and terpenoids being also found. Nonanol, 2,6-nonadienal, 1-hexanol, 2-hexenal, and D-limonene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Even though prickly pears have no strong aroma, up to 61 compounds have been identified [32]. In a recent research [31], the studied cultivars showed aldehydes and terpenes as the most numerous compounds. Both chemical groups and alcohols were the most abundant compounds.…”
Section: Volatile Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though prickly pears have no strong aroma, up to 61 compounds have been identified [32]. In a recent research [31], the studied cultivars showed aldehydes and terpenes as the most numerous compounds. Both chemical groups and alcohols were the most abundant compounds.…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…These compounds usually show a low concentration in fruits and their variability depends on cultivar, climatological conditions, maturity and storage conditions, among other factors [30]. In prickly pear fruit pulp, the content of these compounds varies from 3.33 mg 100 g −1 to 14.86 mg 100 g −1 [31]. Even though prickly pears have no strong aroma, up to 61 compounds have been identified [32].…”
Section: Volatile Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rodrígues et al [26] investigated the volatile compounds of the fruit pulp of different Opuntia species and showed undecane, phenylethyl alcohol, and pentyl acetate as major volatile constituents of O. ficus-indica. Very recently Andreu-Coll et al [27] extracted a total of 35 compounds from O. ficus-indica fruits: 10 aldehydes (for example, 2,6-nonadienal), 8 terpenes (β-myrcene), 7 esters (methyl-3-hexenoate), 6 alcohols (nonanol), 1 ketone (1-penten-3-one), 1 linear hydrocarbon (5-undecene), and 1 terpene (linalool). In fresh and dried fruits of Opuntia dilleniid, 56 and 43 volatile compounds, respectively, were identified with esters (6.38%), aldehydes (41.79%), alcohols (17.82%), ketones (13.39%), and alkanes (9.20%) as main classes of compounds.…”
Section: Introductionmentioning
confidence: 99%